Psychological adaptation of Polish Olympic level athletes to the conditions in China - psychological conditions of the Jet Lag Phenomenon - Pisarek, A.; Selwant, K.; Jaroslaw, K. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: The main objective of the research was to determine the impact of time zone change on readiness to perform from a psychological perspective. Effective adaptation was deemed to be such psychophysical condition of the athlete at which a start at their maximum level of training is possible. Apart from the typical jet lag syndrome which occurs, it has been shown that early and effective adaptation has also been influenced by psychological variables (such as: fear level in three situations, personal capabilities, mood, situational and start-related stress, or the variables investigated into in the adaptation questionnaire, such as: frame of mind, attitude towards training and starting, and adaptation selfassessment. Methods Olympic team athletes (male and female) in weight lifting, canoeing, archery and modern pentathlon participated in the study when performing in China and Thailand. The following psychological tests were completed during the athletes stay ranging from 2 days to 2 weeks: UMACL, STAI- X1, KomP. The Adaptation Questionnaire and Coach Assessment of the training plan were also completed. Intragroup and intergroup examinations were conducted as well as variable analyses in situations before and after the start within the groups researched into, or comparison of groups participating in Olympic qualifications or not. Results / Discussion The level of adaptation to the conditions was highest within the canoers' group. Adaptation is positively related to the athlete's experience, age and stay duration. Athlete's experience significantly affects the level of self-assessment of the adaptation by the athletes. Within the archers' group, sports results positively correlated with the coach's opinion, athlete's self-assessment and subjective feeling of good adaptation. This indicates a good level of adaptation within the group. Within all the groups researched, an observed correlation between the start's assessment by the coach and self-assessment of the adaptation to start was evident, which indicates a relation between effective adaptation and high results achieved. Participation in the contest is of tremendous importance to the level of anxiety as a condition. Within the archery and women's weight lifting groups, the level of anxiety and emotional tension clearly decreased following the start. The canoers do not feature that dependence - the level of anxiety at all times remained comparable but the athletes did not qualify for the Olympics - they were in the period of detraining. There is also a significant relationship between the coach`s assessment at the start and the level of the athlete`s anxiety before the start (the higher the level of anxiety is the worse results the athlete achieves). Conclusions In professional athletes, it was not physiological jet lag that was of the greatest importance but managing the difficult start-related situations, that is the Olympic qualification aspect. The research conducted has enabled coaches, who obtained feedback from the research team, to plan their departure to the Olympic Games allowing for the time and mental capabilities necessary to achieve the optimum adaptation status of their athletes from a psychological approach.